2015
DOI: 10.1001/jamaneurol.2015.1424
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modifiers of Age at Onset in Carriers of the G206A Mutation inPSEN1With Familial Alzheimer Disease Among Caribbean Hispanics

Abstract: IMPORTANCE The present study identified potential genetic modifiers that may delay or accelerate age at onset of familial Alzheimer disease (AD) by examining age at onset in PSEN1 mutation carrier families, and further investigation of these modifiers may provide insight into the pathobiology of AD and potential therapeutic measures.OBJECTIVE To identify genetic variants that modify age at onset of AD. DESIGN, SETTING, AND PARTICIPANTS Using a subset of Caribbean Hispanic families that carry the PSEN1 p.G206A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…Studies in knock-out mouse models have established that the gene TCRα has an important role in adult neurogenesis [Huang and others 2010], particularly in the hippocampus, an area of the brain involved in the HAND phenotype. The SH3RF3 gene (and the SH3 domain) has been associated with age of onset in familial Alzheimer’s disease [Lee and others 2015]. At a type I error cut-off of p<10 −4 , 8 SNPs were associated with both binary GDS and continuous GDS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in knock-out mouse models have established that the gene TCRα has an important role in adult neurogenesis [Huang and others 2010], particularly in the hippocampus, an area of the brain involved in the HAND phenotype. The SH3RF3 gene (and the SH3 domain) has been associated with age of onset in familial Alzheimer’s disease [Lee and others 2015]. At a type I error cut-off of p<10 −4 , 8 SNPs were associated with both binary GDS and continuous GDS.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been reported as a genetic modifier affecting both AAO and circulating levels of progranulin in FTD patients carrying Granulin mutations [34, 35]. Another example of genetic modifiers of AAO is the one recently reported in PSEN1 -related Alzheimer’s disease [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein E is one such genetic factor influencing AD, but its role in FTD is unclear and controversial [Bernardi et al, 2006; Seripa et al, 2011; Hernández et al, 2014]. Lee et al [2015] have reported three genes (SNX25, PDLIM3, SORBS2) modifying age of onset in a specific mutation (G206A) in PSEN1 in familial AD, but the effect of these genes in FTD is unknown. A single nucleotide polymorphism (SNP) in TMEM106B has been shown to modify penetrance in GRN- related FTD [Finch et al, 2011] and motor neuron versus behavioral expression in C9orf72 -related ALS/FTD [van Blitterswijk et al, 2014], but reported to have no effect in MAPT-related FTD [Finch et al, 2011].…”
Section: Discussionmentioning
confidence: 99%